قروض البنك الدولي وأثرها على التنمية الاقتصادية في الدول العربية - حيدر عفيف; بلول صابر; عماد أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2013)
على الرغم من أن التنمية الاقتصادية احتلت مكان الصدارة في اهتمامات الدول العربية، إلا أن تمويل تلك التنمية قد استأثر بالجانب الأكبر من ذلك الاهتمام في ضوء قصور رأس المال الذي يعدّ ضرورياً لانطلاق الاقتصاد إلى مرحلة النمو الذاتي المنشودة من تلك الدول، مما جعلها تتجه إلى مصادر خارجية للتمويل تتمثل في منح الإعانات والقروض الخارجية والاستثمارات الأجنبية المباشرة وغير المباشرة، لسد فجوتي الموارد المحلية والنقد الأجنبي. ولقد اقتصر هذا البحث على دراسة أحد أهم أشكال التمويل الخارجي وهو القروض المقدّمة من البنك الدولي وأثره على التنمية الاقتصادية في الدول العربية. ولقد توصل البحث إلى أن البنك الدولي ينتهج سياسات الدول الكبرى من حيث تقديم القروض للدول التي يتوفر فيها مصالح استراتيجية اقتصادية وسياسية، كما أن لتدفق رؤوس الأموال إلى الدول العربية من البنك الدولي سواء في صورة منح أو قروض، تكون مرتبطة بشروط تصب في صالح ضمان حقوق ومصالح الدول الدائنة. وبناءً على ذلك فإن السياسة المالية التي يتبعها البنك الدولي من خلال القروض الممنوحة للدول العربية تعدّ من أهم العوامل التي تكرّس مفهوم التّبعية. In Spite of the fact that economic development has occupied the leading position in the interests of the Arab countries, the funding of that development has taken the larger area of that interest in the light of the deficiency in the capital which is considered necessary in the launching of economy to the self-development phase. This has led Arab countries towards the foreign sources for funding represented in aids, foreign loans and direct and indirect foreign investments to fill the gap in the local resources and the foreign currency. This paper aims at studying one of the forms of foreign funding which is the loans from the International Bank and their effects on the economic development in the Arab countries. The paper concludes that the International Bank follows the policies of the big countries in terms of giving loans that provide political, economic and strategic interests. Besides, the flow of the capitals to Arab countries whether in the form of gifts or loans is related to conditions that are in favor of guaranteeing the interests of creditor countries. In this way, the financial policy of the International Bank through the loans it gives to the Arab countries is one of the most important factors that ensures the concept of subordination.